A problemática da regressividade da tributação indireta em face das injustiças fiscais ocasionadas pelo vigente Sistema Constitucional Tributário Brasileiro - Lírio, Isabelle Jaíne Gonçalves (2018)
The present dissertation aims to analyze the problem of the regressive effect of consumption taxation in the face of the current Brazilian constitutional system. Being considered high, this taxation, which has the nature of regressive collection, more severely burden the poor and economically disadvantaged, which causes a series of problems, such as fiscal regressivity and income concentration, eventually increasing economic and social inequalities. social policies. The fiscal injustices caused by the imbalances of the tax system hinder human development and diminish the effectiveness of public policies. In effect, the Brazilian Constitution was the principiological paradigm used to build the theoretical foundations necessary for a critical analysis of the national tax system. The path used to prepare the dissertation was composed of an analysis of taxation for consumption in Brazilian law, where the social context and the scientific framework of the research were studied through a bibliographical and qualitative literature. The fight against excesses committed by the State through indirect tax collection must be accomplished through the restructuring of the tax system, which reduces the collection of taxes inserted in products, avoiding the notorious regressivity of Brazilian taxation. Tax justice has been studied in the face of the application of the principles derived from fundamental rights constitutionally foreseen, using theoretical axes such as Amartya Sen, so that, from a human development perspective, in which the human being must be able to choose the resources necessary to develop and achieve the position you want in society in a free way. Tax justice must be achieved.